A Pragmatic Approach to Dry Eye Diagnosis: Evidence into Practice. Issue 12 (December 2015) - Downie, Laura E.; Keller, Peter R.
Abstract : ABSTRACT: Dry eye disease (DED) is a common, multifactorial disease of the tears and anterior ocular surface. The clinical diagnosis of DED is complex, requiring the consideration of both patient symptoms and signs, which can be apparently contradictory. Misdiagnosis can lead to suboptimal clinical management. Studies of the practice behaviors of optometrists suggest that there is the potential to improve the translation of research evidence relating to the diagnosis of DED into primary ophthalmic care. This review describes an evidence-based, pragmatic approach to the contemporary clinical diagnosis of DED, as a means for guiding best practice for the care of dry eye patients.